Malignant infarction of the right medial cerebral artery due to embolism from an atrial myxoma. A case report - Vélez, Jorge Luis (2019)
Cardiac myxoma is a benign neoplasm, when it is located in the left atrium it is potentially associated with systemic embolism, and it is a rare cause of cerebral embolism. The diagnosis of cardiac myxoma is usually incidental, being found as a result of searching for other clinical conditions. We present the case of a patient who probably had a cardiac myxoma of the left atrium that induced a malignant infarction in the territory of the left medial cerebral artery, bedside heart ultrasound was a relevant diagnostic procedure in this patient.